염화칼슘 처리에 의한 엘크 암사슴의 뿔 발생 유도에 관한 연구 - 김상우; 이승수; 최순호; 상병돈; 김영근; 상병찬; 서길웅; 문상호; Kim, Sang-Woo; Lee, Seung-Soo; Choi, Sun-Ho; Sang, Byong-Don; et al. (Journal of animal science and technology, 2008)
To investigate the effects of CaCl2 on artificial induction of antlerogenesis in female deer, various CaCl2 conditions with different concentrations, dosages and times were treated to five female Elk(Cervua Canadensis). After injection of CaCl2 solution to the putative region of antlerogenesis, rate of induction, yield of antler, length of antler, number of point were examined. In regard to the effect of concentration of CaCl2 solution on the induction of antlerogenesis in the female deer, generation of pedicle and antler has not induced under treatment of 2ml and 3ml of 15％ solution, but only pedicle has generated with 4ml of 15％ solution, otherwise generation of pedicle and antler has induced under treatment of 1.5ml, 2ml and 3ml of 30％ solution and 1ml and 2ml of 50％ solution. The yields of antler were 319g in 4ml of 15％ solution, and 1,290g, 513g and 295g in 1.5ml, 2ml and 3ml of 30％ solution, respectively, and 800g and 443g in 1ml and 2ml of 50％ solution, respectively. The yields of antler of 30％ solution and 50％ solution were decreased with increase the dosage volume. The maximum yield of antler was 1,290g at 30％ 1.5ml treatment. The length of antler were 25cm in 15％ 4ml treatment, and 55cm, 51cm and 35㎝ in 1.5ml, 2ml and 3ml of 30％ solution, respectively, and 60cm and 35cm in 1ml and 2ml 50％ solution, respectively. There was a tendency that length of antler became longer as yield of antler were grew. The numbers of point were 2 in 15％ 4ml treatment, and 5, 2.3 and 1 in 1.5ml, 2ml and 3ml of 30％ solution, respectively, and 3 and 1 in 1ml and 2ml of 50％ solution, respectively. The number of point was not related to concentration and dosage of CaCl2 solution, but related to the shape of wound due to the time and method of injection. Consequently, the optimum concentration of CaCl2 solution for artificial induction of antlerogenesis in female elk is 30%. 본 연구는 자연 상태로는 뿔이 발생하지 않는 암사슴에서 인공적으로 뿔 발생을 유도하기 위하여 동물의 조직을 괴사시키는데 사용되는 CaCl2 용액을 뿔 발생 예정부위인 좌우 양측 두개 골막에 주사하여 뿔 발생 여부 및 CaCl2 농도와 주사량이 뿔 발생 유도에 미치는 영향을 구명하고자 하였다. 공시축은 엘크 암사슴 5두이다. 엘크 암사슴에 15％용액 2ml 및 3ml를 처리한 시험구에서는 육경과 뿔 발생이 모두 유도되지 않았으며, 15％용액 4ml 처리구와, 30％용액 1.5ml, 2ml, 3ml구 및 50％용액 1ml, 2ml 구에서는 육경과 뿔 발생이 모두 유도되었다. 뿔 생산량은 30％용액 1.5ml 처리구에서 1,290g로 가장 많았으며, 주사량이 증가할수록 뿔 생산량이 줄어드는 경향을 보였다. 발생한 가지수는 15％용액 4ml 처리구는 2개, 30％용액 1.5ml, 2ml 및 3ml 처리구는 각각 5개, 2.3개 및 1개였으며, 50％용액 1ml 및 2ml 처리구는 각각 3개 및 1개로 농도 및 주사량과 가지수는 관련이 없었다. 오히려 초기 가지수의 발생은 주사 횟수 및 주사방법의 차이에 의한 상처부위의 모양에 따라 결정되는 경향을 보였다. 이상의 결과에서 30% CaCl2 용액이 엘크 암사슴의 육경 및 뿔 발생과 그 생산량 및 가지수에 가장 적합한 농도였다.